Effect of the large-scale green tide on the species succession of green macroalgal micro-propagules in the coastal waters of Qingdao, China. (January 2018) - Miao, Xiaoxiang; Xiao, Jie; Pang, Min; Zhang, Xuelei; Wang, Zongling; Miao, Junwei; Li, Yan
Abstract: In order to evaluate the effect of the large-scale green tide on micro-propagule community in the coastal waters of Qingdao, a year-round survey was conducted to investigate the abundance and species succession of the green macroalgal micro-propagules. Five Ulva and one Blidingia species were detected and an evident shift on species composition was observed in summer when the large-scale floating biomass of Ulva prolifera approached the coasts of Qingdao. Propagules of U. prolifera were only dominant in summer. Detection of the 'floating' type of U. prolifera in summer, a unique strain responsible for the green tide in Yellow Sea, supported that large-scale floating U. prolifera biomass could affect local micro-propagule community. There were, however, no 'floating' U. prolifera propagules were detected in the following winter, indicating that influence from the large-scale green tide was transient, and it has not leave prolonged seeds in Qingdao coastal waters. Highlights: The abundance of green macroalgal propagules in coastal water of Qingdao showed seasonal variation. The species composition shifted abruptly in summer when the large-scale floating Ulva prolifera emerged. The 'floating' type of U. prolifera was only detected in summer, while not in other seasons.